Electronics for artists : adding light, motion, and sound to your artwork - Field, Simon (Simon Quellen) (Chicago, Illinois : Chicago Review Press, 2015)
"With today's modern technology--LEDs, servomotors, motion sensors, speakers, and more--artwork can incorporate elements of light, sound, and motion for dramatic effects. Author and educator Simon Quellen Field has developed a primer for creative individuals looking for new ways to express themselves though electronically enhanced art"--
Includes index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2015. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Art and electronics; Art -- Technique; Electronic books